الوظيفة المحور عند المتوكل بين إعمال النبر و إهماله - عبابة, البشير (جامعة الوادي - University of Eloued, 2019)
ملخص: يتناول هذا البحث قضية مهمّة من قضايا نظرية النحو الوظيفي, و هي قضية إسناد الوظيفة المحور داخل الجملة أو الخطاب كما يراها أحمد المتوكل, و ما يعتريها من تحوّلات أثناء عملية التخاطب, سواء أ كان الأمر على مستوى التركيب أم على مستوى الدلالة, أم تعلّق الأمر بكيفية استعماله نطقا وما يصحب ذلك من ظواهر صوتية ترتكز على مكونات معينة كعملية إسناد النبر, والتداخلات التي يمكن أن تحدث نتيجة ذلك مع مكونات أخرى من مكونات الجملة, إضافة إلى تبيين أنواع المحاور التي يمكن أن تكون موجودة في الخطاب, و حالات إسناد النبر الحاصل فيه, مع محاولة توضيح ذلك من خلال تبيين الأسباب الناتجة عن هذه العملية و الدلالات المستخلصة منها. Abstract: This research deals with an important issue of the theory of functional grammar, which is the issue of assigning the pivotal function within the sentence or speech as seen by Ahmed Al-Mutawakil, focusing on the changes that occur during the process of communication, whether it is at the syntax level of or the level of meaning, or how it can be used in pronunciation as well as the acoustic phenomena based on certain components such as the process of attaching the stress , in addition to the interactions that can occur as a result with other components of the sentence, in addition to the identification of the types of main topics that can be found in the discourse, showing the cases of stress that took a place, With an attempt to clarify this by showing the reasons and resulting that could be derived from it.
مقال
Keywords: محور؛ نبر؛ وظيفة؛ تخاطب؛ تداول; axis؛ stress؛ function؛ addressing؛ circulation